(untitled) (Development Service Industry Management, 2025)
The authors have clarified the essence of enterprise performance, analyzed the approaches to determining and managing efficiency, as well as the indicators and criteria for measuring it. Particular attention was given to the differences between the concepts of “efficiency” and “effectiveness”. The authors emphasized that in modern conditions, one of the key indicators of efficiency is the growth of the market value of a business in the long term, since the company’s systemic focus on creating long term value is the basis for competitiveness in a dynamic market environment. The article identifies value-based indicators that can be used in the process of implementing value-based management. It is substantiated that the growth of enterprise value is a strategic goal that reflects its sustainability, profitability and investment attractiveness. The authors also outlined the main directions for ensuring the growth of the enterprise’s value and methods for increasing the enterprise’s investment attractiveness. In addition, the authors noted that from an investor’s perspective, the value of a company is one of the components of investment attractiveness. It allows to understand the structure of the business and predict its future income. Value-based management and investment management are related concepts, where the first defines the strategic goal and the second provides the tools to achieve it. Without effective investment management, value-oriented management remains only an abstract concept, and vice versa, without the strategic goal of maximizing value, investment management can be reduced to simply selecting the most profitable projects, which do not always correspond to the long-term interests of the company. In conclusion, it is stated that enterprise valuation performs a dual function: it not only determines the market price of a company, but also acts as a reliable indicator of its performance. In today’s world, where competition is not only for customers but also for capital, systematic valuation is becoming an essential element of strategic management.